Gut Microbiota Dysbiosis in Acute Ischemic Stroke Associated With 3-Month Unfavorable Outcome - Sun, Huanhuan; Gu, Mengmeng; Li, Zhongyuan; Chen, Xiangliang; Zhou, Junshan (Frontiers in Neurology, 2022)
Background: Alterations in the gut microbiota after ischemic stroke have been demonstrated, whereas the effect on stroke outcome remains to be established. Methods: A total of 132 consecutive patients with acute ischemic stroke were prospectively enrolled. Their gut microbiomes within 24 hours of admission were profiled using 16S rRNA gene (V3-V4 region) sequencing. Microbiota comparisons were made between groups with good outcome (n = 105) and poor outcome (n = 27) based on 3-month modified Rankin Scale scores of 0-2 and 3-6. Propensity score-matching (PSM) analysis was conducted to assess the robustness of our findings. The functional potential was predicted using the Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt). Results: Patients in the poor outcome group were characterized by a significant reduction in the alpha diversity (Shannon index, p = 0.025; Simpson index, p = 0.010), an increase in the pathogenic bacteria (e.g., Enterococcaceae and Enterococcus), and a decrease in the short-chain fatty acids (SCFAs)-producing bacteria (e.g., Bacteroidaceae, Ruminococcaceae and Faecalibacterium) to those with good outcome group (all p < 0.05). Similar results of microbial composition were obtained after PSM. The PICRUSt revealed that the pathway for membrane transport was relatively dominant in patients with poor outcome (p < 0.05). Conclusion: Our study demonstrated that stroke patients with 3-month poor outcome had baseline gut microbiota dysbiosis featured by increased pathogenic bacteria and decreased SCFAs-producing bacteria.